Warning Triggers in Environmental Hazards: Who Should Be Warned to Do What and When?. Issue 4 (13th July 2016) - Cova, Thomas J.; Dennison, Philip E.; Li, Dapeng; Drews, Frank A.; Siebeneck, Laura K.; Lindell, Michael K.
Abstract : Determining the most effective public warnings to issue during a hazardous environmental event is a complex problem. Three primary questions need to be answered: Who should take protective action? What is the best action? and When should this action be initiated? Warning triggers provide a proactive means for emergency managers to simultaneously answer these questions by recommending that a target group take a specified protective action if a preset environmental trigger condition occurs (e.g., warn a community to evacuate if a wildfire crosses a proximal ridgeline). Triggers are used to warn the public across a wide variety of environmental hazards, and an improved understanding of their nature and role promises to: (1) advance protective action theory by unifying the natural, built, and social themes in hazards research into one framework, (2) reveal important information about emergency managers' risk perception, situational awareness, and threat assessment regarding threat behavior and public response, and (3) advance spatiotemporal models for representing the geography and timing of disaster warning and response (i.e., a coupled natural‐built‐social system). We provide an overview and research agenda designed to advance our understanding and modeling of warning triggers.